Immunomodulatory role of azithromycin: Potential applications to radiation-induced lung injury - Yan, Yujie; Wu, Leilei; Li, Xuefei; Zhao, Lan; Xu, Yaping (Frontiers in Oncology, 2023)
Radiation-induced lung injury (RILI) including radiation-induced pneumonitis and radiation-induced pulmonary fibrosis is a side effect of radiotherapy for thoracic tumors. Azithromycin is a macrolide with immunomodulatory properties and anti-inflammatory effects. The immunopathology of RILI that results from irradiation is robust pro-inflammatory responses with high levels of chemokine and cytokine expression. In some patients, pulmonary interstitial fibrosis results usually due to an overactive immune response. Growing clinical studies recently proposed that the anti-inflammatory and immunomodulatory effects of azithromycin may benefit patients with acute lung injury. It has been shown potential benefits for patients with RILI in preclinical studies. Azithromycin has a variety of immunomodulatory effect to improve the process of disease, including inhibition of pro-inflammatory cytokines production participating in the regulatory function of macrophages, changes in autophagy, and inhibition of neutrophil influx. We review the published evidence of mechanisms of azithromycin, and focus on the potential effect of azithromycin on the immune response to RILI.